Study On Awareness About Entrepreneurship Development Program Among Youth - Kalra, Isha; Sehrawat, Parul (Journal of Advanced Research in English & Education, 2020)
Entrepreneurs are considered as agents of economic growth. They create wealth, generate employment, provide new goods and services and raise the standard of living. In recent years, entrepreneur and Entrepreneurship Development Programme (EDP) has become a serious matter of discussion about meaning of entrepreneur, characteristics of entrepreneur, role of entrepreneur in economic growth etc. An EDP equips entrepreneurs and makes them competent to anticipate and deal with a variety of problems that any entrepreneur may have to face. It gives confidence to the entrepreneur to face uncertainties and take profitable risks. It prepares them to deserve and make good use of various forms of assistance. EDP helps in dispersal of economic activities in different regions by providing training and other support to local people. The optimum use of natural, financial and human resources can be made in a country by training and educating the entrepreneurs. This research paper carried on the bases of perception of 100 consumers which personally interviewed through questionnaire. After doing the study some conclusions and recommendation are also given in the paper. How to cite this article: Kalra I, Sehrawat P. Study on Awareness about Entrepreneurship Development Program among Youth. J Adv Res Eng & Edu 2020; 5(4): 12-18